Robust and Fuzzy Optimisation Models for a Flow shop Scheduling Problem with Sequence Dependent Setup Times: A real case study on a PCB assembly company - Gholami-Zanjani, Seyed Mohammad; Hakimifar, Mohammadmehdi; Nazemi, Najmesadat; Jolai, Fariborz (International journal of computer integrated manufacturing, 2017)
In this paper, authors considered a flow shop scheduling problem with sequence dependent set-up times in an uncertain environment. Its objective function is to minimise weighted mean completion time. As for uncertainty, set-up and processing times are considered not to be deterministic. Authors propose two different approaches to deal with uncertainty of input data: robust optimisation (RO) and fuzzy optimisation. First, a deterministic mixed-integer linear programming model is presented for the general problem. Then, its robust counterpart of the proposed model is dealt with. Afterwards, the fuzzy flow shop model is developed. Moreover, a real case study on Tehran-Madar Company which is a producer of printed circuit board and OEMs is studied. Finally, a considerable discussion is held on comparison of all three approaches of namely deterministic, fuzzy and ROs based on some generated numerical examples.